Comparative Study between RIPASA Scoring System and ALVARADO Scoring System in Diagnosing Acute Appendicitis in Adults - Hameed, Aous; Alaraji, Hameed Hussein (AL-Kindy College Medical Journal, 2023)
Background: Acute appendicitis is regarded as one of the most common inflammation that needs surgical intervention. Different scoring systems have been used for diagnosing of acute appendicitis. ALVARADO score is one of the most widely used score in diagnosing of acute appendicitis, but the accuracy of the latter is insufficiently low in Middle-East patients. Thus a new scoring system called RIPASA score has been designed for diagnosing of acute appendicitis in those patients. The aim of this study is to use RIPASA score and compare its result with ALVARADO score in diagnosing of acute appendicitis. Subjects and Methods: The study includes 200 patients with symptoms and signs of acute appendicitis in Al-Kindy Teaching Hospital/Baghdad/Iraq from 1st of November 2017 to 30th of November 2018. The variables of both scoring systems are registered for each patient included in this study and all patients who are underwent appendectomy their specimens are sent for histopathology. Results: The study includes 200 patients with suspicion of acute appendicitis. By applying both scores for each patient, then comparing the result of the two scores with the histopathology reports; RIPASA score has shown sensitivity, specificity, and diagnostic accuracy (93.6%, 74.4%, 89.5%) more than ALVARADO score (82.8%, 65.1%, 79%) respectively. The area under the receiver operating characteristic (ROC) curve of RIPASA score (0.957) is higher and significantly better than that of ALVARADO score (0.893) with P value <0.05. Conclusions: The RIPASA score is more sensitive, more specific, and has high diagnostic accuracy than ALVARADO score.